The New US Military Strategy and Behavioral Wars - E. Larina; V. Ovchinsky (Международная аналитика, 2015)
The Article is devoted to new nonconventional types of weapon, in the accelerated order of the defensive innovations developed in the USA according to Strategy of national security the 2015 and Third initiative defense innovation. Practical steps on creation of new type of behavioral weapon, laying on a joint of use of technologies of Big Data, intellectual calculations and last achievements of social and behavioral psychology are analyzed.